Effect of monopolar capacitive resistive radiofrequency in treating stress urinary incontinence: A pilot randomized control trial - Elhosary, Eman A.; Ahmed Hamada, Hamada; Ali AlMubali, Fatimah; López Sánchez, Guillermo F.; Ahmed, Sara M. (Frontiers in Psychology, 2023)
Objective: To assess the effectiveness of 448 kHz monopolar capacitive resistive radiofrequency (MCRR) in the treatment of females with stress urinary incontinence (SUI) and its impact on self-esteem. Methods: Forty females with SUI were separated randomly into two equal groups. Group A with 20 females received the MCRR therapy for 20 minutes and performed pelvic floor exercises for 20 minutes. Group B with 20 females received placebo treatment by applying the same application as in Group A without emitting any waves for 20 minutes, three times a week, for four weeks. Both groups were assessed by a perineometer to assess the strength of the pelvic floor muscles (PFM), the visual analogue scale (VAS), and the Incontinence Symptom Severity Index. In addition, the impact of the treatment on self-esteem was measured with an ad hoc questionnaire. Results: There was a significant reduction (p < 0.05) in VAS and the Incontinence Symptom Severity Index and a significant increase in the strength of the PFM in both groups post-treatment compared with the pre-treatment. Regarding between-subject effects, there was a significant difference in VAS, the Incontinence Symptom Severity Index, and the perineometer between both groups (p < 0.05), and this significant improvement favored Group A. The impact of the treatment on self-esteem was also positive (p < 0.05). Conclusion: MCRR and pelvic floor exercises are more effective methods for the treatment of SUI than just pelvic floor exercises, and this combined treatment has a positive impact on the self-esteem of females with SUI.